Thermal delay provided by floors containing layers that incorporate expanded cork granule waste (Energy and Buildings, 2014)
This paper reports the computation of the thermal delay provided by concrete floors built with layers of cork and lightweight screed that incorporate expanded cork granule waste. The heat transfer by conduc- tion across these multilayer systems is simulated analytically under unsteady boundary conditions. The thermal delay is computed for multilayer concrete floors with varying numbers of layers and layer thicknesses. The mass density and thermal conductivity of the various materials were determined experi- mentally. Given its heterogeneity, the specific heat of the lightweight screed was obtained indirectly using both the experimental results and the analytical model. The results obtained show the potential of these composites in applications for increasing the thermal performance of concrete floors, in particular the thermal delay and thermal resistance. The results show that the contribution of the insulating lightweight screed material’s properties to thermal delay is more relevant in systems composed of few layers. The constructive solutions composed of a greater number of layers present higher thermal delay value.